2021
DOI: 10.3390/polym13183107
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Light-Curable Calcium-Silicate-Containing Composites Used in Odontogenic Regeneration

Abstract: Pulp regeneration is one of the most successful areas in the field of tissue regeneration, despite its current limitations. The biocompatibility of endodontic biomaterials is essential in securing the oral microenvironment and supporting pulp tissue regeneration. Therefore, the objective of this study was to investigate the new light-curable calcium silicate (CS)-containing polyethylene glycol diacrylate (PEGDA) biocomposites’ regulation of human dental pulp stem cells (hDPSCs) in odontogenic-related regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, our data suggest that higher C3S content may not directly translate into higher DTS as this property is also governed by the presence and reactions of other components like dicalcium silicate and aluminates, currently present as major or minor phases in commercial products (Primus et al 2019). Hence, further research shall unveil the effects arising from the interaction of these components on cement’s properties (Lin, Shie, et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, our data suggest that higher C3S content may not directly translate into higher DTS as this property is also governed by the presence and reactions of other components like dicalcium silicate and aluminates, currently present as major or minor phases in commercial products (Primus et al 2019). Hence, further research shall unveil the effects arising from the interaction of these components on cement’s properties (Lin, Shie, et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results showed that inclusion of calcium silicate (CS) products into GelMa were able to enhance angiogenesis via increasing the secretion of VEGF from fibroblasts [20]. In fact, CS is the bioceramic that is always used as an endodontics material for root repair [21]. This was due to the sustained and gradual release of silicate (Si) and calcium (Ca) ions into the surrounding fluid upon degradation and immersion [22].…”
Section: Introductionmentioning
confidence: 99%